Ethnic Differences in Duration and Timing of Exposure to Neighbourhood Disadvantage during Childhood - Tom Kleinepier; Maarten van Ham (Institute of Labor Economics (IZA), 2017)
This paper examines ethnic differences in childhood neighborhood disadvantage among children living in the Netherlands. In contrast to more conventional approaches for assessing children's exposure to neighborhood poverty and affluence (e.g., point-in-time and cumulative measures of exposure), we apply sequence analysis to simultaneously capture the timing and duration of exposure to poor and nonpoor neighborhoods during childhood. Rich administrative microdata offered a unique opportunity to follow the entire 1999 birth cohort of the Turkish, Moroccan, Surinamese, and Antillean second generation and a native Dutch comparison group from birth up until age 15 (N=24,212). Results indicate that especially Turkish and Moroccan children were more likely than native Dutch children to live in a poor neighborhood at any specific stage within childhood, but particularly throughout childhood. Although differences became substantially smaller after adjusting for parental and household characteristics, ethnic differences remained large and statistically significant. In addition, the impact of household income on children's neighborhood income trajectories was found to be weaker for ethnic minority children than for native Dutch children. Our findings are discussed in relation to theories on spatial assimilation, place stratification, and residential preferences.
Keywords: I30; J60; P46; R23; 330; childhood; ethnicity; life course; neighborhood; sequence analysis